Application of the Total Productive Maintenance to Increase the Overall Value of Equipment Effectiveness on Ventilator Machines - Hibarkah Kurnia; Andini Putri Riandani; Tri Aprianto (Jurnal Optimasi Sistem Industri, 2023)
This article has been corrected.  Please see the https://josi.ft.unand.ac.id/index.php/josi/announcement/view/41  for details.